MENTORING AS ONE OF THE PREREQUISITES FOR THE DEVELOPMENT OF THE ENTREPRENEURIAL ENVIRONMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The quality of the entrepreneurial environment is one of the preconditions for the competitiveness of the national economy of Latvia. Mentoring in entrepreneurship is mainly used to foster the expansion of new and less-experienced enterprises. Cooperation between a mentor and a mentee gives opportunities for the mentee to grow and develop. The paper is based on the implementation results for the research grant "Mentoring Opportunities for Entrepreneurship Development in Rezekne Municipality”. The research aim is to examine mentoring as one of the preconditions for the development of the entrepreneurial environment. The research results revealed that mentoring could be one of the most effective ways how to promote an increase in the number of entrepreneurs and economic growth. Potential mentors rated a mentor’s knowledge of relevant business legislation and how to enter a new market and attract a new cooperation partner as “important” and “very important”. Mentees, in contrast, wished to make new contacts, acquire new cooperation partners and attract investments and funds with the help of their mentors as well as expected that their mentors would help them to reveal their personal potential and how to effectively use it in entrepreneurship. The key traits needed by mentees, the potential mentors referred to, confirmed the theoretical principles of mentoring – mentors have to hear and listen and to help their mentees to find answers to problems themselves. In Rezekne municipality, mentoring in entrepreneurship could contribute to the development of less-experienced enterprises. Accordingly, it is necessary to continue the research begun by the authors, identifying and creating a database of potential mentors and mentees in the other municipalities of Latgale region who can and are ready to engage in the business mentor network. Research methods used: monographic and descriptive, analysis, synthesis, statistical analysis and a sociological method – surveying. The research was done based on relevant research studies by foreign and national scientists as well as industry experts, data of the Central Statistical Bureau and other information sources.